A selected outlook : a report by the Committee on Science, Engineering, and Public Policy of the National Academy of Sciences, National Academy of Engineering, Institute of Medicine. (San Francisco, 1983)
Prepared at the request of the National Science Foundation"-P. Includes bibliographies and index.
Keywords: Công nghệ,Technology